An analysis of the expansion of the prophet’s mosque by Caliph ‘Uthman b. ‘Affan (d. 36 AH/656 CE) - Omer, Spahic (ISTAC, IIUM, 2016)
This paper discusses the expansion of the Prophet’s Mosque in Madinah by Caliph ‘Uthman b. ‘Affan. The paper concludes that in terms of architectural morphology and structural configuration, the expansion was a historic and ground-breaking event. It set a new architectural standard in the nascent Muslim society, which was used as a benchmark for future trends and comparisons. The discussion revolves around two main thrusts: the expansion between a sentimental penchant and architectural pragmatism; and the expansion as an important phase in the evolution of the identity of Muslim architecture. These are dealt with after the main physical aspects of the expansion have been described. The paper provides several essential lessons in their crude form on the significance and meaning of Muslim architecture, especially insofar as such perennial issues as form-function relationship, the role of spirituality, public participation, sustainable development and tradition-versus-modernity dialectics, are concerned. ‘Uthman advocated such an architectural philosophy as was anchored in originality, progressivism and pragmatism, in the process remaining faithful both to his personal spiritual impulses and the pressing requirements of the dynamic evolution of Muslim architecture and civilization.